The Macroeconomics of the Credit Crisis: In Search of Externalities for Macro-Prudential Supervision - Frank A.G. den Butter (Tinbergen Institute, 2010)
In the analysis of the credit crisis of 2007-2010 a clear distinction should be made between (i) the initial shock; (ii) the propagation and amplification of the initial shock to the systemic crisis of the financial markets; and (iii) the transmission of the credit crisis to the real economic sector causing a major cyclical downturn now known as the great recession. This paper argues that banking supervision failed to anticipate and repair the market failure that caused the huge amplification of the relatively small initial shock. As the repair of market failure is the only sound economic argument for regulation, banking supervisors should now focus on the externalities that caused the amplification of the shock and use that knowledge for adequate macro-prudential supervision in the future. Macro-economic models can be helpful in this search for externalities. The character and timing of future shocks are unpredictable, but contagion in the propagation mechanisms should be mitigated as much as possible.
Keywords: E42; E58; G38; 330; credit crisis; externalities; macro-prudential supervision; contagion; fallacy of composition; Liquiditätsbeschränkung; Ansteckungseffekt; Kreditgeschäft; Bankenaufsicht; Wirkungsanalyse; Welt